Investigations on Antibacterial Potency of Azadirachta Indica Leaf Extracts against Some Resistant Bacteria - N. B. Awandekar; Kalyani Game; M. J. Umekar (International Journal of Pharma and Bio Sciences, 2021)
Resistance to antibiotics in pathogens responsible for causing infectious diseases has become a matter of great public health concern internationally and India is no exception to it. Widespread use and availability of practically all the antimicrobials across the counter and incompletion of the dose is supposed to be one of the major reasons for this. It is observed that some plant extracts seem to potentiate the activity of antibiotics against resistant bacterial strains. So the objective of the study was to use some natural products as an alternate to the conventional treatment against antibiotic resistance. The effects of crude extracts of leaves of Azadirachta indica against resistant strains of pathogenic S. aureus, E. coli and K. Pneumoniae were investigated using the agar well diffusion method. It was observed that the growth of all the isolates were inhibited to varying degrees with gram-positive more susceptible than gram-negative bacteria. Hexane extract was more effective, producing larger zones of growth inhibition sizes and smaller MIC, than the aqueous and ethyl acetate extracts. The MIC values ranged from 0.5 - 4 mg/ml. The ability of the crude extracts to inhibit the growth of such resistant pathogenic bacterial strains that were used in this study is an indication that the neem leaves extract has the potential and can be used as a source for new broad spectrum oral antibiotics. The result obtained in this study validates the use of the neem leaves extract in traditional medicine to treat infectious conditions.